input(x): a number

output(y): 2 less than 4 times x
use the function rule to complete the table
input(x) output(y)
-1 ?
0 ?
1 ?
2 ?

To find the values for output (y) for different input (x) using the given function rule, we substitute the values of x into the function rule and solve for y.

Given that the function rule is 2 less than 4 times x, we can write it as:
y = 4x - 2

Now, let's substitute the given values of x into the function rule to find the corresponding values of y:

For x = -1:
y = 4(-1) - 2
y = -4 - 2
y = -6

For x = 0:
y = 4(0) - 2
y = 0 - 2
y = -2

For x = 1:
y = 4(1) - 2
y = 4 - 2
y = 2

For x = 2:
y = 4(2) - 2
y = 8 - 2
y = 6

Hence, the completed table would look like this:

input(x) output(y)
-1 -6
0 -2
1 2
2 6

To find the output for each given input using the function rule, you need to substitute the value of x into the expression "2 less than 4 times x" and simplify it.

Let's go through each input value step by step:

For the first input (-1):
To find the output, substitute x = -1 into the expression:
y = 4 * (-1) - 2
Now simplify the expression:
y = -4 - 2
y = -6

For the second input (0):
To find the output, substitute x = 0 into the expression:
y = 4 * 0 - 2
Now simplify the expression:
y = 0 - 2
y = -2

For the third input (1):
To find the output, substitute x = 1 into the expression:
y = 4 * 1 - 2
Now simplify the expression:
y = 4 - 2
y = 2

And finally, for the fourth input (2):
To find the output, substitute x = 2 into the expression:
y = 4 * 2 - 2
Now simplify the expression:
y = 8 - 2
y = 6

Now you have the outputs for each of the given inputs. The completed table will look like this:

input(x) | output(y)
-1 | -6
0 | -2
1 | 2
2 | 6

To complete the table using the function rule "2 less than 4 times x", we can substitute each value of x into the function rule and simplify the expression.

For x = -1:
y = 2 less than 4 times (-1)
y = 2 - 4
y = -2

For x = 0:
y = 2 less than 4 times 0
y = 2 - 0
y = 2

For x = 1:
y = 2 less than 4 times 1
y = 2 - 4
y = -2

For x = 2:
y = 2 less than 4 times 2
y = 2 - 8
y = -6

Using the function rule, we can complete the table as follows:

input(x) output(y)
-1 -2
0 2
1 -2
2 -6